Capability Of Adsorptive Expoxified Poly(Ethersulfone) Membrane To Separate Chromium Ions - Tan, Ying Shien (Universiti Sains Malaysia, 2017)
A microporous epoxy resin epoxified-polyethersulfone (EPES) blend membrane (EPES membrane) was prepared through dry-wet phase inversion. This study attempts to correlate the changes in membrane physical and chemical properties when different composition (30wt%, 50wt%, 70wt% and 90wt %) of bisphenol A diglycidyl ether (BADGE) were added into the PES membrane. The synthesised membrane was used to separate the carcinogen chromium (VI). Analysis from fourier transform infrared spectroscopy (FTIR) has proved the present of the epoxy peak which indicated the successful integration of the epoxy resin into the polymer matrix. Scanning electron microscopy (SEM) showed the finger-like pore structure in neat PES and sponge structure pore in EPES membrane. Also, the macrovoid became more significant as the composition of BADGE increases. Moreover, the viscosity of the dope solution of each formula were found lower when more BADGE added which explain the phenomenon observe in SEM as viscosity will affect the rate of diffusion of NMP solvent during phase inversion. The lower viscosity allow the rate of diffusion higher and thus increased the macrovoid phenomenon. As the performances of the membranes, permeate flux increased with reduction of fouling when composition of BADGE was increased. 30wt% of BADGE/PES membrane show highest rejection of Cr (VI) ions at 83.734% with permeated flux of 1.52 L/m2.min. In this work, another type of epoxy resin- Glycidyl methacrylate (GMA) was also used as the additive and compare the performance with BADGE/PES membrane. The GMA-PES membrane demonstrated very high initial flux of 89.312 L/m2.min but very low rejection at 19.067%. Through FTIR analysis, GMA peak was failed to appear, indicated most of the epoxy resin was fluxed out during the membrane synthesis. It was due to the high solubility of GMA in water as compared to BADGE.